Дикая Лиза: [роман] / Ирина Мельникова - Мельникова Ирина Александровна (Вера, надежда, любовь, 2007)
Экземпляры: ф.3 (20191111) / Инвентарный номер: 59895 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: М 48 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44